YOUTH EMPOWERMENT IN OPTIMIZING OF WIROTAMAN AMPELGADING VILLAGE BRANDING AS A TOLERANCE EDUCATION VILLAGE - Destriana Saraswati; Mohamad Anas; Kurniawan (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is known as a country with a diversity of cultures, ethnicities, and religions. On one hand, this diversity can be seen as a potential. But on the other hand, religious and ethnic diversity can sometimes cause friction in society. Currently, digital technology such as social media plays a role in maintaining and spreading conflicts related to diversity. Therefore, an effort is needed to create educational content related to inter-religious tolerance. One of them is through the branding of the tolerance village which can provide real examples related to people's lives with religious diversity. Wirotaman Village, Ampelgading, Malang Regency, which is known to have a community with religious diversity, is an appropriate target. Through community service activities, a team from Universitas Brawijaya invites youth who are members of Karang Taruna to brand Wirotaman Village as a village of tolerance. The service is carried out through training on the use of sosial media as a means of branding and the preparation of educational content regarding religious tolerance. The method applied is a participatory approach and interactive learning through training. As a result, the youth of Wirotaman Village are educated about the potential of Wirotaman Village, as well as the importance of using sosial media as a means of branding and village progress. In addition, the youth of Wirotaman Village also gain knowledge in content creation and social media management which they can use as a means of education, especially with regard to tolerance in society.